Pengaruh Crude Ekstrak Bunga Nangka (Artocarpus heterophyllus Lamk.) Terhadap Ekspresi Outer Membrane Protein (OMP) Salmonella typhi - I Nengah Kundera; Faisal Abdurahman (JIMR - Journal of Islamic Medicine Research, 2017)
Crude extracts of Jackfruit (Artocarpus heterophyllus Lamk) flowers contain antibacterial compounds such as alkaloids, tannins, flafonid and steroids, which is alsoempirically useful as medicine for diarrhea. This research is aiming to determine the efficacy of antibacterial exposure of crude extract of A. heterophyllus Lamk flowers, and the change of outer membrane protein (OMP) expressions protein virulence factors of Salmonella typhi. The results indicate that the crude extract of A. heterophyllus Lamk. Flowers has antibacterial efficacy against S. typhi at the lowest concentration of 20%, since at this concentration crude extract of A. heterophyllus Lamk. flowers is still capable of inhibiting the growth of S. typhi. Based on the results of SDS-PAGE electrophoresis and measurement of protein molecular weight, it is found that several OMP molecular weights are 80 kDa, 66kDa, 57 kDa, 45 kDa, 36 kDa, 33 kDa, 30 kDa, 28kDa, 23 kDa, 20 kDa, 16 kDa, 14 kDa and 10kDa based on the low standard marker protein product [zigma]. It is confirmed that the exposure to crude extract of flower A. heterophyllus Lamk. results in the changes of OMP protein expression of S. typhi compared to the normal OMP expression. This finding is supported by the inhibition on the growth and activity of S.typhi in the test of antibacterial properties of extracts jackfruit A.heterophyllus Lamk. flowers.Keyword : Salmonella Typhi, omp, A.hterophyllus Lamk.